DEIKSIS DALAM NOVEL DARI HARI KE HARI KARYA MAHBUB DJUNAIDI - Yunita Eka Pratiwi; Rinjani Edelweiska; Dodi Firmansyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The purpose of this research is to describe the types of deixis in the novel from Dari Hari ke Hari by Mahbub Djunaidi. The research method used in this research is descriptive with qualitative research type. The technique used in analyzing deixis in the novel Dari Hari Ke Hari is using the technique of simak catat. The research conducted shows that in the novel Dari Hari Ke Hari by Mahbub Djunaidi there are six types of deixis, namely: 1) persona deixis is divided into three parts, namely, first persona deixis, second persona deixis, and third persona deixis. First person deixis consists of: I, me, we, and us. Second person deixis consists of: thou, you, your, and you guys. Third person deixis consists of: he, she, she, and they. 2) Place deixis consists of there, there, here. 3) Time deixis consists of yesterday, tomorrow, and the day after tomorrow. 4) discourse deixis refers to the use of terms such as